Happiness-lost: Did Governments make the right decisions to combat Covid-19? - Talita Greyling; Stephanie Rossouw; Tamanna Adhikari (Global Labor Organization (GLO), 2020)
Amidst the rapid global spread of Covid-19, many governments enforced country-wide lockdowns, with likely severe well-being consequences. The actions by governments triggered a debate on whether the well-being and economic costs of a lockdown surpass the benefits perceived from a lower infection rate. In this regard, South Africa is an extreme case: enforcing very stringent lockdown regulations, while amid an economic crisis. We analyse the impact of both Covid-19 and the lockdown on happiness. We use the Gross National Happiness Index to compare the determinants of happiness before and after the Covid-19 lockdown regulations. Further, we estimate the likelihood of happiness levels in 2020, reaching the average levels in 2019 using two models; one predicting the likelihood after the lockdown was enforced and the other if no lockdown regulations were in place. The results shed light on happiness outcomes in a scenario of lockdown versus no lockdown.
Keywords: C55; I12; I31; J18; 330; Happiness; Covid-19; Big data; Regulations; Probabilities; South Africa